2010
DOI: 10.18569/tempus.v4i2.795
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and HIV risk related practices in the Brazilian population aged to 15 to 64 years old, 2008.

Abstract: O artigo tem por objetivo apresentar os principais resultados da Pesquisa de Conhecimentos, Atitudes e Práticas na população brasileira, realizado em 2008. Foi realizado inquérito domiciliar de âmbito nacional com amostra probabilística stratificada cada por macrorregião geográfica e situação urbana e rural. Os achados apresentados apontam para a necessidade de investimento contínuo e sistemático em ações que assegurem à população em geral o acesso à informação, aos insumos de prevenção e ao diagnóstico precoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…However, the third factor also reduces the likelihood that men who occasionally have unprotected sex would be included in the group at great risk, which leads to the underestimation of the size of this group. In this regard, a national household survey conducted in Brazil in 2008 which enquired about sexual practices over the previous 12-month period (Pascom et al, 2011) showed that relations with casual partners (36.8%) and certain sexual relations without condoms (74.5%) were more frequent than indicated by the results observed in this study.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…However, the third factor also reduces the likelihood that men who occasionally have unprotected sex would be included in the group at great risk, which leads to the underestimation of the size of this group. In this regard, a national household survey conducted in Brazil in 2008 which enquired about sexual practices over the previous 12-month period (Pascom et al, 2011) showed that relations with casual partners (36.8%) and certain sexual relations without condoms (74.5%) were more frequent than indicated by the results observed in this study.…”
Section: Discussioncontrasting
confidence: 47%
“…The predominance of a ‘conjugal interaction’ pattern was also reported among Brazilian women in two national household surveys. In these studies, the percentage of women with stable partners during the previous year varied between 95% and 89% (Barbosa and Koyama, 2008; Pascom et al, 2011). Other countries in which the HIV epidemic has similar features to that of the epidemic in Brazil also show a pattern consistent with the one observed in this study.…”
Section: Discussionmentioning
confidence: 99%